Jawabanmu

2014-01-02T13:52:22+07:00
(  \sqrt{8} + 8 ^{ \frac{-6}{3} }   )   ^{ \frac{2}{3} } 

= 8 ^{ \frac{1}{2} X  \frac{2}{3}  }  + 8 ^{ \frac{-6}{3} X  \frac{2}{3}  } 

= 8  ^{ \frac{2}{6} } + 8  ^{ \frac{-12}{3} } 

= 2 ^{3}  ^{X} ^{ \frac{1}{3} } + 2    ^{-4} ^{X} ^{2} 


 
= 2/ 2^{8}
2014-01-02T14:23:27+07:00
( ( \sqrt{8} ÷ 8  \frac{-6}{3} ) \frac{2}{3}
= 8  \frac{1}{2} ×  \frac{2}{3} ÷ 8 \frac{-6}{3} ×  \frac{2}{3}
= 8 \frac{2}{6 } ÷ 8  \frac{-12}{3}
= 2^{3} ×  \frac{1}{3} ÷  2^{-4} × 2
= 2 ÷  2^{-8}
= 1
   8
1 4 1